TECHNOLOGY OF CONTINUOUS MANUFACTURE OF ELECTRODES FOR LEAD-ACID BATTERIES - Dzenzerskyi, V. O.; Burylov, S. V.; Skosar, V. Yu.; Skosar, Yu. I.; Anikeiev, Ye. V.; Neznanov, M. O. (Science and Transport Progress, 2007)
We have developed the technology of the continuous manufacturing of leads for lead-acid batteries. The said technology allows increasing the corrosion resistance, the mechanical strenght of leads and the lifetime of batteries.